Enhancing Student Services: Machine Learning Chatbot Intent Recognition for High School Inquiries - Assayed, Suha Khalil (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)